Token Economy Application for Reduced Online Gaming Duration in Adolescents: Aplikasi Ekonomi Token untuk Mengurangi Durasi Bermain Game Online pada Remaja - Siti Mahmudah; Ghozali Rusyid Affandi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Rapid technological development has positioned online gaming as a dominant leisure activity among adolescents, frequently associated with excessive daily use and behavioral difficulties. Specific Background: Prolonged online gaming duration among junior high school students has been linked to disrupted learning routines, social withdrawal, and neglected daily activities, necessitating structured behavioral interventions grounded in behavioral psychology. Knowledge Gap: Although token economy strategies have been widely applied to address addictive behaviors in children and adults, empirical evidence using single subject research designs focusing specifically on adolescent gaming duration remains limited, particularly with detailed phase-based observation. Aims: This study aimed to examine the application of a token economy technique to reduce the duration of online gaming behavior in a 13-year-old junior high school student. Results: Using a quantitative quasi-experimental single subject research design with an ABA structure, the findings demonstrated a consistent reduction in gaming duration from an initial range of 6–12 hours during baseline to approximately 2–3 hours in the post-intervention phase, accompanied by increased behavioral stability. Novelty: The study presents detailed within-condition and between-condition analyses illustrating behavioral change patterns across baseline, intervention, and withdrawal phases within a home-based setting. Implications: These findings suggest that token economy techniques can serve as a structured behavioral modification approach for managing excessive online gaming duration among adolescents, with practical relevance for parents and practitioners implementing behavior-based interventions. Highlights: Daily Gaming Time Showed a Clear Downward Trend Across Structured Observational Phases. Behavioral Stability Increased Following the Reinforcement-Based Intervention. Home-Based Reinforcement Procedures Supported Sustained Behavioral Change. Keywords: Token Economy, Online Gaming Duration, Adolescents, Single Subject Research, Behavior Modification